2016
DOI: 10.1136/archdischild-2016-311143
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and socioeconomic variation in incidence of congenital heart defects

Abstract: IntroductionEthnic differences in the birth prevalence of congenital heart defects (CHDs) have been reported; however, studies of the contemporary UK population are lacking. We investigated ethnic variations in incidence of serious CHDs requiring cardiac intervention before 1 year of age.MethodsAll infants who had a cardiac intervention in England and Wales between 1 January 2005 and 31 December 2010 were identified in the national congenital heart disease surgical audit and matched with paediatric intensive c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
74
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(79 citation statements)
references
References 31 publications
1
74
1
3
Order By: Relevance
“…31 Previous studies revealed ethnic disparities in incidence. [32][33][34] However, we found no significant differences between TBMs and FBMs. Instead, children of rural TBMs had the highest incidence, perhaps because of the higher prevalence of alcohol misuse in rural areas.…”
Section: Discussioncontrasting
confidence: 79%
“…31 Previous studies revealed ethnic disparities in incidence. [32][33][34] However, we found no significant differences between TBMs and FBMs. Instead, children of rural TBMs had the highest incidence, perhaps because of the higher prevalence of alcohol misuse in rural areas.…”
Section: Discussioncontrasting
confidence: 79%
“…There are also several studies showing that the incidence of congenital abnormalities tend to be decreasing in last decade (Yu et al, ). Ethnic differences may also play a role in the incidences of certain congenital abnormalities (Knowles et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Participants could also only comment on the support and information needs of families who contacted the helpline, which is likely to result in the needs of some parents not being represented, such as those of parents from non‐English speaking populations or parents who were less able – for financial, social or other reasons – to contact the helpline. From previous work , we know that children from ethnic minorities are over‐represented in the CHD population and yet these are the families who are least likely to access support. A further limitation was that not every participant had experience in each of the areas covered by the interview – for example, one helpline staff member had not taken any calls in relation to discharge after surgery but they had spoken to many parents about sources of support once families were back home.…”
Section: Discussionmentioning
confidence: 99%
“…There is a wealth of evidence about the psychological impact of the diagnosis of CHD and subsequent treatment on parents , but far less is documented about the specific concerns of parents once their child is discharged from hospital. As part of a larger study looking at infants with complex CHD who have been discharged home, which included interviews with parents and health professionals , we wanted to interview helpline staff from a number of charities providing support to families of children with CHD to understand their experiences of talking to families whose baby had recently been discharged after infant cardiac surgery. We specifically wanted to elicit their perceptions of the key reasons/issues/concerns that families called the helpline to discuss in relation to their baby's cardiac surgery.…”
Section: Introductionmentioning
confidence: 99%